Effects of post-curing conditions on degree of conversion, microhardness, and stainability of 3D printed permanent resins - Sultan Aktug Karademir; Samet Atasoy; Serdar Akarsu; Eda Karaaslan (BMC Oral Health)
Abstract Background The aim of this in-vitro study is to investigate the effect of post-curing time and units on the degree of conversion (DC), microhardness (VHN) and staining susceptibility (∆E00) of two 3D printed permanent resins (Crowntec (SCT), Varseosmile CrownPlus (VSP)). Methods A total of 180 disc-shaped samples (10*10*2 mm), 60 for each experiment, from the tested materials (30 SCT, 30 VSP) were printed on 3D printer. Half of the samples were post-cured in LC-3DPrint Box and the other half in Phrozen Cure V2 and were divided into 3 subgroups according to post-curing time of 5, 10 and 30 min (n = 5). The DC of the samples was determined using a Fourier transform infrared spectrometer. The VHN values were measured with a Vickers hardness tester. The color of the samples was initially measured using a spectrophotometer and then again after one month of staining in coffee. The ∆E00 was calculated with the CIEDE2000 formula. Data obtained from each parameter examined were analyzed by SPSS software using One-Way ANOVA, post-hoc Tukey, post-hoc Tamhane’s T2, Independent-samples T test and Pearson’s correlation test (α = 0.05). Results While DC and VHN ​​of the tested materials increased in parallel with the post-curing time, ∆E00 decreased. The highest DC (74.6 ± 3.8) and VHN (29.1 ± 0.8) and the lowest ∆E00 (1.9 ± 0.1) were obtained in LC-3DPrint Box-30 min post-curing group of VSP. The effect of the type of post-curing units on the DC and ∆E00 of the materials was statistically significant (p < 0.05) except for the SCT-5 min and SCT-30 min groups. The VHN was statistically significantly higher in LC-3DPrint Box at all post-curing times of the tested materials (p < 0.05). A significant positive correlation was found between DC and VHN (r = 0.796, p < 0.001), while a significant negative correlation was observed between DC and ∆E00 (r=-0.763, p < 0.001). Conclusion The study demonstrated that extending the post-curing time led to improvements in the degree of conversion and microhardness, while simultaneously reducing the stainability of the materials tested. Additionally, the type of post-curing unit used had a significant impact on these results, further highlighting the importance of both curing time and equipment in optimizing material properties.